Multi-stage ozonation and biological treatment for the removal of azo dye industrial effluent - Nazerry Rosmady, Rahmat; Fahmi Muhammad, Ridwan; Che Zulzikrami, Azner Abidin; Apipah, Ariffin (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.